EVALUATION OF CHOROIDAL AND MACULAR THICKNESS ASSESSED BY ENHANCED DEPTH IMAGING SD-OCT IN THE NATURAL PROGRESSION OF MYOPIC PATIENTS. - Das, Matuli; Sahu, Pallavi; Desai, Devanshi (Student’s Journal of Health Research Africa, 2025)
Background Myopia is associated with structural changes in the retina and choroid, which can be assessed using enhanced depth imaging spectral-domain optical coherence tomography (SD-OCT). This study aimed to evaluate the changes in choroidal and macular thickness among patients with varying degrees of myopia. Methods A cross-sectional observational study was conducted at Pradyumna Bal Memorial Hospital, Kalinga Institute of Medical Sciences (KIMS), KIIT University, Bhubaneswar, India. A total of 74 participants (148 eyes) with myopia were recruited. Participants underwent SD-OCT imaging, and measurements of macular and choroidal thickness were taken. Data were analyzed based on age, gender, and degree of myopia. Results There was a significant reduction in retinal and choroidal thickness with increasing age (p < 0.05). High myopia (> -9 diopters) showed significantly thinner retinal and choroidal layers compared to low and moderate myopia groups (p < 0.01). Male participants had slightly higher thickness measurements compared to females, but the difference was not statistically significant. Conclusion Progression of myopia is associated with thinning of retinal and choroidal structures, particularly in patients with high myopia. Recommendation Regular SD-OCT monitoring is recommended in myopic patients for early detection of structural changes and timely intervention.